MEMBANGUN DAN MENANAMKAN JIWA WIRAUSAHA PADA REMAJA DI DESA DARUREJO KECAMATAN PLANDAAN KABUPATEN JOMBANG - Kurniawan, Indra (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
Instilling an entrepreneurial spirit from adolescence is a major investment for the country in order to achieve prosperity and prosperity. Instilling an entrepreneurial spirit can be done through education and training, both through formal and non-formal studies. This activity was carried out among teenagers in Darurejo Village, Plandaan District, Jombang Regency with the aim of instilling an entrepreneurial spirit such as independence, creativity, innovation, ability to work in a team, responsibility and output, having practical skills to see and take advantage of opportunities to start a business. Based on the results of the activities carried out, young entrepreneurs in Darurejo Village were enthusiastic in carrying out activities, creative and innovative during discussions with resource persons, and already had an idea of ​​the product to be created